Inquiry-based learning in science and mathematics - WYNNE HARLEN (Metaichmio Publications, 2013)
This paper sets out strong arguments in favour of inquiry-based education in science and mathematics in terms of benefits to individuals and to society. It draws on research and other sources, such as the publications of the Fibonacci project, to define inquiry and model the development of understanding through inquiry. The rather sparse evidence of the effectiveness of inquiry-based approaches is cited, noting the need for valid means of assessing the outcomes of inquiry. The final section considers the role that student assessment can take both in supporting and in reporting learning through inquiry and changes in current assessment practices that are needed.